Characterization of events associated with apoptosis/anoikis induced by snake venom metalloproteinase BaP1 on human endothelial cells - Díaz Oreiro, Cecilia (2005)
Human endothelial EA.hy926 cells were incubated with BaP1, a hemorrhagic metalloproteinase purified from Bothrops asper snake venom. Since the first hour of incubation with the proteinase, cells started showing DNA fragmentation, detected by a terminal deoxynucleotidyl transferase-mediated dUDP nick-end labeling (TUNEL)-based photometric enzyme-linked immunosorbent assay (ELISA). At later times, DNA fragments were predominantly located outside the cells, evidencing plasma membrane rupture. DNA fragmentation was completely abolished by Batimastat, a potent inhibitor of metalloproteinase enzymatic activity. Apoptosis induced by BaP1 on endothelial cells was independent of two Bcl-2 family members (anti-apototic Bcl-xL and pro-apoptotic Bax), that did not show any changes in their expression during a 24 h-treatment period. Interestingly, IkappaBalpha, an inhibitor of NFkappaB, decreased after 24 h of treatment, suggesting further activation of the transcription factor. When some elements of the apoptotic extrinsic pathway were assessed, it was observed that procaspase-8 completely disappeared after 24 h of treatment with BaP1, probably indicating its activation by a death receptor, whereas caspase-8 inhibitor, cellular FLICE-inhibitory protein (cFLIP(L)), increased its expression since the first hours of BaP1 incubation. In conclusion, treatment of human endothelial cells with BaP1 induces apoptosis/anoikis, independently of Bcl-2 family members Bax and Bcl-xL and associated with caspase-8 activation and cFLIP(L) up-regulation. Apoptosis was completely dependent on BaP1 enzymatic activity. Similarities between this and other endothelial cell anoikis-related systems suggest that BaP1 and other snake venom metalloproteinases may be useful experimental tools in the study of death-related events that occur when adherent cells loose contact with extracellular matrix.